018 Neuroferritinopathy: a new finding in a novel disease. Issue 3 (9th February 2012) - Keogh, M; Jones, P; Coulthard, A; Chinnery, P F; Burn, J
Abstract : Introduction: Neuroferritinopathy is an adult onset autosomal dominant movement disorder which occurs due to a mutation in the ferritin light chain gene (FTL1). This mutation results in abnormal iron accumulation in the brain. Though the disease presents in middle age, little is known about the temporal relationship between iron accumulation and symptomatic presentation. Methods: A prospective double blind MRI trial was performed of first degree relatives of known carriers of pathological FTL1 mutations. The coded MRI images were sent to a radiologist in Australia who was blind to the results of the genetic analysis on the same subjects. Results: Eleven subjects completed the MRI scans and were stratified by age: 6–16 yrs (n=4); 17–25 yrs (n=3); 26–36 yrs (4 n=4). Three subjects had abnormal studies. In each case the signal abnormality in the basal ganglia was readily visible on T2* MRI images, and all three participants orived to be gene positive for the c.460insA mutation in the FTL1 gene: The youngest was aged 6 years old. Discussion: Neuroferritinopathy is regarded as an adult onset movement disorder, however patients actually begin to deposit iron within their basal ganglia from early childhood. This disorder should be regarded as a cause of iron deposition in infants, and when effective pharmacological interventions are established, carriers of mutations in the ferritin light chain gene will need to consider early treatment commencement.